Vanillin conversion by aldol condensation using hydrotalcite Mg-Al and modified-Y zeolite as heterogeneous catalysts - Thai, Nguyen Thi; Thu, Nguyen Thi Minh (Vietnam Journal of Science and Technology, 2021)
Mg-Alhydrotalcite, MgO-Al2O3 mixed oxides and modified-Y zeolite (sulfated Y zeolite and copper ion-exchanged Y zeolite) were prepared and characterized by XRD, EDX and XRF techniques. These materials were used as heterogeneous catalysts in aldol condensation of vanillin and acetone.The obtained results showed that the heterogeneous acid catalysts as modified-Y zeolites were more effective than the heterogeneous base catalysts as hydrotalcite Mg-Al and MgO-Al2O3 mixed oxides in aldol condensation reaction of vanillin. The highest conversion of vanillin was 95.5% when the reaction was carried out at 120oC in 5 hours, using sulfated Y zeolite.